2019
DOI: 10.3390/biology8020049
|View full text |Cite
|
Sign up to set email alerts
|

Affinity Isolation and Mass Spectrometry Identification of Prostacyclin Synthase (PTGIS) Subinteractome

Abstract: Prostacyclin synthase (PTGIS; EC 5.3.99.4) catalyzes isomerization of prostaglandin H2 to prostacyclin, a potent vasodilator and inhibitor of platelet aggregation. At present, limited data exist on functional coupling and possible ways of regulating PTGIS due to insufficient information about protein–protein interactions in which this crucial enzyme is involved. The aim of this study is to isolate protein partners for PTGIS from rat tissue lysates. Using CNBr-activated Sepharose 4B with covalently immobilized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 56 publications
0
9
0
2
Order By: Relevance
“…In previous publications, it was shown that both thromboxane and prostacyclin synthases had formed stable molecular complexes with a number of protein partners (Ershov et al, 2019a; Gnedenko et al, 2019; Svirid et al, 2017). Taken together, the SPR‐validated PPIs are shown schematically in Figure 1.…”
Section: Binary Ppis Involving Cyp5a1 and Cyp8a1mentioning
confidence: 99%
See 2 more Smart Citations
“…In previous publications, it was shown that both thromboxane and prostacyclin synthases had formed stable molecular complexes with a number of protein partners (Ershov et al, 2019a; Gnedenko et al, 2019; Svirid et al, 2017). Taken together, the SPR‐validated PPIs are shown schematically in Figure 1.…”
Section: Binary Ppis Involving Cyp5a1 and Cyp8a1mentioning
confidence: 99%
“…At the same time, CYP8A1 formed molecular complexes with other microsomal (CYP21A2 and CYP2J2) and mitochondrial (CYP11A1 and CYP11B1) cytochrome P450s. Negative results of direct complex formation between CYP5A1 and CYP8A1 as well as between these synthases and cytochrome P450's redox partners (CYB5A, CPR, and Adx), which are strong binders of different CYP isoenzymes, were obtained (Ershov et al, 2019a; Yablokov et al, 2019). It is quite obvious that the CPR protein, isolated from the liver tissue, using CYP5A1 as a bait, could be a protein partner of co‐isolated CYP2D10 (Table 1).…”
Section: Binary Ppis Involving Cyp5a1 and Cyp8a1mentioning
confidence: 99%
See 1 more Smart Citation
“…Содержание общего белка в образцах тканевого лизата определяли по методу Бредфорда. Диссоциацию белковых комплексов тканевого лизата выполняли согласно протоколу [3].…”
Section: реактивы и препаратыunclassified
“…Было выявлено, что почти три четверти всех идентифицированных во фракциях белков находятся в виде гомо-и гетеродимерных комплексов и белковых комплексов более высокого порядка. Также в работах [2,3] был продемонстрирован оригинальный способ диссоциации интактных белковых комплексов лизата, заключающийся в кратковременной кислотной обработке лизата с последующей нейтрализацией, для увеличения чувствительности и специфичности прямого молекулярного фишинга белковых партнеров целевого белка. Вместе с тем, остается пока неизвестным, насколько отличается обычный SEC профиль белков/белковых комплексов лизата от профиля ре-ассоциированных белков обработанного лизата.…”
unclassified